2005
DOI: 10.1097/01.rli.0000178837.68891.f2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Testicular Viability by Power Doppler Ultrasonography in Experimentally Induced Acute Testicular Torsion

Abstract: Preoperative US including power Doppler examination can predict testicular viability in testicular torsion. Echogenicity of nonviable testes was found to be hypoechoic and inhomogeneous. Power Doppler examination showed no or intermittent peripheral blood flow in nonviable testes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Previously, it has been shown that color Doppler examination is useful for prognosis in dogs with splenic torsion 15 . Also, the progress of a testicular torsion could be predicted by examination of the blood flow pattern 16 . Color Doppler examination of blood flow patterns in inflamed glands appears to be useful in predicting therapy outcome as a reduction in blood flow is associated with the development of a necrosis in the affected gland.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that color Doppler examination is useful for prognosis in dogs with splenic torsion 15 . Also, the progress of a testicular torsion could be predicted by examination of the blood flow pattern 16 . Color Doppler examination of blood flow patterns in inflamed glands appears to be useful in predicting therapy outcome as a reduction in blood flow is associated with the development of a necrosis in the affected gland.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not use power Doppler to determine the causes of ABF in the testis. However, the power Doppler and CDU appear to have equivalent sensitivity in the diagnosis of torsion [13]. Third, we also did not use CEUS to determine the causes of absent blood flow in the testis.…”
Section: Discussionmentioning
confidence: 98%
“…Allerdings ist anzumerken, dass die Bestimmung des Blutflusses im Gewebe in anderen Fragestellungen der Veterinärmedizin bereits ihren prognostischen Stellenwert bewiesen hat. So konnten Kwon et al (16) bei Ratten mit einer Hodentorsion eine verminderte Durchblutung des Hodenparenchyms mit einer beginnenden Nekrose in Verbindung bringen. Auch im Zusammenhang mit einer Milztorsion ist der Einsatz der Farbdoppler-Sonographie bekannt (23).…”
Section: Diskussionunclassified